Infill development strategies for Block A of Xushen gas field. (2015) - Xu, Qinglong; Li, Haijiang; Guo, Guanghui; Zhang, Ye
Along with the enhancement of oil and gas exploration technologies, a large scale of natural gas reservoir of volcanic rock was discovered deep in the north of Songliao Basin of China. The gas reservoir has several distinct features such as diversified rock types, complex lithology, fast change of lithofacies, existence of micro-fractures, poor rock physical properties and strong heterogeneity, etc. Then a multidisciplinary method was used to evaluate the volcanic rock lithology and lithofacies, validity of matrix and fractures, types of pore space and its connection to factures. Based on above mentioned studies, optimisation was carried out on the development mode, layer series division, well pattern and its interspacing, gas production rate, stable production time and final recovery ratio. Also, a reasonable development programme was made. In order to reduce the risk in this programme, such development strategies which proved to highly efficient and have yielded good results were adopted as the overall deployment and successive implementation, pilot well infilling test in priority at local area, highlighted trace evaluation and timely adjustment. [Received: October 29, 2012; Accepted: July 12, 2013]